Introduction to Digital Forensics: Educational Initiatives Through Webinars And Workshops on Recovering Lost Files in the Windows Operating System - Saleh, Oldi Alfani Sunan; Maulana Saputra, Reza Ade; Maulana, Rizky; Haryanda, Muhammad; Mujiastuti, Rully; Sutrisno, Mirza; Hasbi, Muhammad; Adharani, Yana; Rosanti, Nurvelly (Society : Jurnal Pengabdian Masyarakat, 2025)
A webinar and workshop titled "Introduction to Digital Forensics" was held online on July 12, 2025, to improve public understanding of digital data security. Twenty participants attended the event, which included both a pre-test and a post-test. Results showed an increase in participant understanding, with scores on volatile data increasing from 73.7% to 88.2%, on non-volatile data from 72.2% to 82.4%, and on the definition of digital forensics from 84.2% to 88.2%. Furthermore, participant satisfaction was high, with 60% scoring excellent and 30% scoring good. This event was deemed successful in providing a basic understanding of digital forensics and raising awareness of the importance of data protection in the digital age.